Von Willebrand Factor Antigen Predicts Response to Double Dose of Aspirin and Clopidogrel by PFA-100 in Patients Undergoing Primary Angioplasty for St Elevation Myocardial Infarction. (19th December 2013) - Gianetti, Jacopo; Parri, Maria Serena; Della Pina, Francesca; Marchi, Federica; Koni, Endrin; De Caterina, Alberto; Maffei, Stefano; Berti, Sergio
Abstract : Von Willebrand factor (VWF) is an emerging risk factor in acute coronary syndromes. Platelet Function Analyzer (PFA-100) with Collagen/Epinephrine (CEPI) is sensitive to functional alterations of VWF and also identifies patients with high on-treatment platelet reactivity (HPR). The objective of this study was to verify the effect of double dose (DD) of aspirin and clopidogrel on HPR detected by PFA-100 and its relation to VWF and to its regulatory metalloprotease ADAMTS-13. Between 2009 and 2011 we enrolled 116 consecutive patients with ST elevation myocardial infarction undergoing primary PCI with HPR at day 5 after PCI. Patients recruited were then randomized between a standard dose (SD, n = 58 ) or DD of aspirin and clopidogrel (DD, n = 58 ), maintained for 6 months follow-up. Blood samples for PFA-100, light transmittance aggregometry, and VWF/ADAMTS-13 analysis were collected after 5, 30, and 180 days (Times 0, 1, and 2). At Times 1 and 2 we observed a significantly higher CEPI closure times (CT) in DD as compared to SD (P < 0.001 ). Delta of CEPI-CT ( T 1 - T 0 ) was significantly related to VWF (P < 0.001 ) and inversely related to ADAMTS-13 (0.01). Responders had a significantly higher level of VWF at T 0 . Finally, in a multivariate model analysis, VWF and ADAMTS-13 in resulted significant predictors of CEPI-CT response (P = 0.02 ). HRP detected by PFA-100 in acute myocardial infarction is reversible by DD of aspirin and clopidogrel; the response is predicted by basal levels of VWF and ADAMTS-13. PFA-100 may be a useful tool to risk stratification in acute coronary syndromes given its sensitivity to VWF.